2005
DOI: 10.4049/jimmunol.174.8.5082
|View full text |Cite
|
Sign up to set email alerts
|

CCL1-CCR8 Interactions: An Axis Mediating the Recruitment of T Cells and Langerhans-Type Dendritic Cells to Sites of Atopic Skin Inflammation

Abstract: Atopic dermatitis represents a chronically relapsing skin disease with a steadily increasing prevalence of 10–20% in children. Skin-infiltrating T cells, dendritic cells (DC), and mast cells are thought to play a crucial role in its pathogenesis. We report that the expression of the CC chemokine CCL1 (I-309) is significantly and selectively up-regulated in atopic dermatitis in comparison to psoriasis, cutaneous lupus erythematosus, or normal skin. CCL1 serum levels of atopic dermatitis patients are significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
142
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(157 citation statements)
references
References 30 publications
12
142
1
1
Order By: Relevance
“…Recently, it was shown that the constitutive chemokine CXCL12 is also secreted by fibroblasts and its secretion is enhanced upon exposure to stress factors, such as hypoxia, irradiation, and burns [21][22][23][24][25]. CXCL12 secretion is not restricted to fibroblasts though, since endothelial cells and DC are also located in the dermis and also secrete CXCL12 [23,26,27]. Low expression of CXCR4, the CXCL12 receptor, was found on the surface of freshly isolated immature LC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that the constitutive chemokine CXCL12 is also secreted by fibroblasts and its secretion is enhanced upon exposure to stress factors, such as hypoxia, irradiation, and burns [21][22][23][24][25]. CXCL12 secretion is not restricted to fibroblasts though, since endothelial cells and DC are also located in the dermis and also secrete CXCL12 [23,26,27]. Low expression of CXCR4, the CXCL12 receptor, was found on the surface of freshly isolated immature LC.…”
Section: Introductionmentioning
confidence: 99%
“…26 and J. A. Gonzalo, Y. Qiu, J. M. Lora, A. AlGarawi, J. L. Villeval, J. Boyce, C. Martinez, G. Marquez, I. Goya, Q. Hamid, et al, submitted for publication) and by a recent study demonstrating CCL1 and CCR8 up-regulation in atopic dermatitis (21). There are also reports suggesting CCR8 expression by CD4 ϩ CD25 ϩ T REG cells, skin-homing CLA ϩ T cells, monocytes, NK cells, and dendritic cells (21,(27)(28)(29)(30)(31)(32).…”
Section: T He T Lymphocyte Pool Consists Of Naive T Cells and Agexpermentioning
confidence: 99%
“…43 In addition, CCL1 is a potent anti-apoptotic factor. 44 The secretion of high amounts of CCL1 by BPA-exposed DCs might amplify certain immune responses by providing survival signals for Th cells and DCs and by recruiting more CCR8…”
Section: Bpa Induces Th2 Response Via Dcsmentioning
confidence: 99%